Pengembangan Chatbot Sederhana Untuk Informasi Akademi Menggunakan Python Dan Flash Untuk Masyarakat - Andhika Fisryansah Ahlief Putra; Samsul Maarif Aceh; Awaluddin Nasution; Muhammad Syahuda Hasibuan; Supiyandi (CV. ITTC INDONESIA, 2024)
In the ever-evolving digital age, information technology has become a key component in various aspects of life, including the education sector. One technology that shows great potential is chatbot, a computer program designed to simulate human conversation. This research aims to develop a simple chatbot that can provide academic information to the community, using the Python programming language and the Flask framework. This chatbot utilizes Natural Language Processing (NLP) technology to understand and respond to user questions. The results show that the chatbot developed by Universitas Islam Negeri Sumatera Utara (UINSU) can improve accessibility and efficiency in the dissemination of academic information. With further improvements in language understanding capabilities and integration with more comprehensive academic databases, this chatbot has the potential to become a very useful tool in the academic environment. This research makes an important contribution in utilizing digital technology to improve educational services and user experience in accessing academic information.